Studi Eksistensi Permasalahan Perkawinan Adat Masyarakat Samin Berdasarkan Perspektif Hukum Perkawinan Di Indonesia, Di Desa Karangrowo Kudus - Nia Malvin Faradila; Syarifaatul Hidayah; Rana Tatsbita Noer (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Marriage is a legal bond between a man and a woman that is recognized by law or certain social norms. Basically, marriage is a social institution that involves a relationship between two individuals with the intention of forming a family. Marriage also plays a crucial role in the social and cultural structure of society. However, the definition and form of marriage can vary across cultures and religions around the world. Some societies recognize marriage according to certain religious rules, while others may place more emphasis on legal or cultural aspects. Marriage regulations in Indonesia are regulated by various laws starting from the age limit and one of them is by recording at the KUA (Office of Religious Affairs). However, some Samin community marriages have their own procedures. Some Samin people with their unique beliefs and traditions carry out marriage procedures in accordance with the norms and customs they believe in, such as the maximum age limit and not recording at the KUA (Office of Religious Affairs). This administrative procedure is still needed as an integral part of Indonesia's national legal structure, this official recording has important significance in the administrative and legal realms and it should be remembered that within the Indonesian legal framework, the provisions regarding the age limit for marriage are still determined by the applicable law, and every community group, including indigenous peoples such as the Samin people, are required to fulfill these requirements.